A estrutura a termo da taxa de juros no Brasil: testando relações de codependência de ordem zero - Stoppini, Gabriel Magalhães (2011)
This paper tests for zero order codependence of spreads derived from the Brazilian term structure of interest rate. The goal is to analyze the existence of linear combinations of the spreads that result in a contemporaneous white noise process. Those linear combinations could be used for future interest rate forecasting given that departures from those stable relationships would imply future movement of interest rates in order to restore equilibrium. The Nelson and Siegel (1987) model is used as theoretical background for the empirical tests. Testing for zero order codependence implies analyzing assumptions on model’s parameters regarding the Brazilian term structure of interest rate. The evidences derived from empirical tests suggest the rejection of the zero order codependence hypothesis and, therefore, the absence of linear combinations above mentioned. This finding can be related to instability periods found in the sample or the presence of codependence of order higher than zero.